Alzheimer’s disease and epilepsy: shared neuropathology guides current and future treatment strategies - Lu, Olivia; Kouser, Taimur; Skylar-Scott, Irina A. (Frontiers in Neurology, 2023)
Epilepsy is a cause of profound disability in patients with Alzheimer’s disease (AD). The risk of being diagnosed with AD increases the risk for epilepsy, and in parallel, a history of epilepsy increases the likelihood of the development of AD. This bi-directional relationship may be due to underlying shared pathophysiologic hallmarks, including decreased cerebrospinal fluid amyloid beta 42 (Aβ42), increased hyperphosphorylated tau protein, and hippocampal hyperexcitability. Additionally, there are practical treatment considerations in patients with co-morbid AD and epilepsy—namely, there is a higher risk of seizures associated with medications commonly prescribed for Alzheimer’s disease patients, including antidepressants and antipsychotics such as trazodone, serotonin norepinephrine reuptake inhibitors (SNRIs), and first-generation neuroleptics. Anti-amyloid antibodies like aducanumab and lecanemab present new and unique considerations in patients with co-morbid AD and epilepsy given the risk of seizures associated with amyloid-related imaging abnormalities (ARIA) seen with this drug class. Finally, we identify and detail five active studies, including two clinical trials of levetiracetam in the respective treatment of cognition and neuropsychiatric features of AD, a study characterizing the prevalence of epilepsy in AD via prolonged EEG monitoring, a study characterizing AD biomarkers in late-onset epilepsy, and a study evaluating hyperexcitability in AD. These ongoing trials may guide future clinical decision-making and the development of novel therapeutics.